Method for producing tantalum powder for capacitor by reducing tantalum oxide with alkaline earth metal

By using magnesium to reduce tantalum oxide in a hydrogen-containing atmosphere, tantalum powder with excellent voltage resistance and specific capacity is prepared, which solves the problems of safety hazards, complex processes and insufficient performance in the prior art, and realizes the material requirements of high-voltage and high-reliability capacitors.

CN119894624AActive Publication Date: 2025-04-25NINGXIA ORIENT TANTALUM INDUSTRY CO LTD
View PDF 26 Cites 0 Cited by

Patent Information

Application Number
CN202480002576.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-04-25
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

In the prior art, when preparing tantalum powder for capacitors, the use of a large amount of alkaline earth metals poses a safety hazard for ignition, the process is complex and the energy consumption is large, and the voltage resistance and specific capacitance of the tantalum powder are not sufficient, making it difficult to meet the needs of high-reliable capacitors.

Method used

Tantalum powder is prepared by reducing tantalum oxide in a hydrogen-containing atmosphere by alkaline earth metal such as magnesium, reducing the use of alkaline earth metal, simplifying the process, omitting the sintering step, and enhancing the sintering by hydrogen, improving the pressure resistance and specific capacity of the tantalum powder.

Benefits of technology

It effectively reduces the safety risk of alkaline earth metal ignition, simplifies the process, improves the voltage resistance and specific capacity of tantalum powder, and is suitable for the manufacturing of high-voltage and high-reliability capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894624A_ABST
    Figure CN119894624A_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing tantalum powder for a capacitor by reducing tantalum oxide through alkaline earth metal. In particular to a method for preparing tantalum powder by reducing tantalum oxide with alkaline earth metal such as magnesium (preferably magnesium particles), which is characterized by comprising the processes of reduction and heat preservation in a hydrogen-containing atmosphere, preferably, the hydrogen-containing atmosphere is pure hydrogen or mixed gas of hydrogen and inert gas; and / or the hydrogen-containing gas is obtained by introducing gaseous hydrogen-containing gas, or is obtained by adding a hydrogen-containing substance and enabling the hydrogen-containing substance to release hydrogen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of smelting rare metal functional materials, and in particular relates to tantalum powder for making high-voltage and high-reliability capacitors and a manufacturing method thereof. Background Art

[0002] Tantalum electrolytic capacitors (hereinafter referred to as tantalum capacitors) have the advantages of high capacity, small size, strong self-healing ability, and high reliability. They are widely used in high-end technical fields such as communications, computers, automotive electronics, medical equipment, radar, aerospace, and automatic control devices. Tantalum powder is the key material for making tantalum capacitors. Only by using tantalum powder for capacitors with higher voltage resistance can tantalum capacitors with better reliability be produced. Therefore, only by continuously developing tantalum powder for capacitors with higher voltage resistance can the tantalum capacitors produced continue to meet the requirements of high-reliability development of electronic devices and electronic circuits.

[0003] At present, the main methods for industrial preparation of capacitor-grade tantalum powder are sodium reduction potassium fluorotantalate method, magnesium reduction tantalum oxide method, tantalum ingot hydrogenation method, etc. The sodium reduction potassium fluorotantalate method can easily prepare high specific capacity tantalum powder, but the problem is that the pressure resistance of tantalum powder is generally low. The tantalum powder prepared by tantalum ingot hydrogenation method has excellent pressure resistance, but the problem is that the specific capacity of tantalum powder is generally low. In order to continuously improve the pressure resistance of tantalum powder and at the same time increase the specific capacity of tantalum powder, the magnesium reduction tantalum oxide method has been successfully developed and continuously developed. The magnesium reduction tantalum oxide method has obvious advantages in preparing tantalum powder for capacitors with improved specific capacity and pressure resistance because it changes the state of the reactants.

[0004] CN114192791B discloses a method for producing tantalum powder for capacitors by reducing tantalum oxide with alkaline earth metal. This method is to add alkali metal or alkaline earth metal halide during the reduction process, use excess alkaline earth metal to reduce at a high temperature above 700°C in a heating furnace filled with inert gas, separate the excess alkaline earth metal from the tantalum-containing material after the reduction, and then further sinter the material at a high temperature above 750°C. However, the problem with this method is that a large amount of alkaline earth metal is used, and fire may occur when the material is taken out of the furnace after reduction, posing a safety hazard. Moreover, the process is relatively complicated, requires a separate sintering step, and consumes a lot of energy.

[0005] CN1308566A (application number 99808374.7), CN105033283A (application number 201510310262.2), and CN1251325A also disclose methods for producing tantalum powder by reducing tantalum oxide with alkaline earth metals (including magnesium vapor) or rare earth metals. However, the tantalum powder produced by these methods has a large specific surface area, strong activity, and poor burning resistance. The tantalum powder for capacitors produced has relatively poor breakdown voltage and specific capacitance after high-voltage empowerment, and does not significantly improve the withstand voltage performance of tantalum powder for capacitors.

[0006] There is also a method of preparing tantalum powder by self-propagating high temperature synthesis (SHS) in the prior art. However, this method needs to be carried out at a temperature of at least 2000°C, and the reaction is too fast, which is not only difficult to control, but also has too high requirements on process equipment. In addition, the obtained tantalum powder is also uneven and cannot meet the needs of manufacturing high-reliability capacitors.

[0007] Without being bound by general theories, the inventors have found through extensive research that the existing tantalum powder preparation process has the potential safety hazard of ignition of alkaline earth metals due to the use of a large amount of alkaline earth metals, and the process is relatively complex and consumes a lot of energy. Moreover, the overall electrical performance is not ideal. Summary of the invention

[0008] An object of the present invention is to provide a method for preparing tantalum powder by reducing tantalum oxide with an alkaline earth metal such as magnesium in a hydrogen-containing atmosphere. The method can reduce the amount of alkaline earth metal added to produce tantalum powder, and the safety risk of alkaline earth metal ignition when it is taken out of the furnace after the reduction is completed is also reduced.

[0009] Another object of the present invention is to provide a method for producing tantalum powder for capacitors which is simple in process, easier to operate and control, and safer in process. Accordingly, the present invention provides a method for preparing tantalum powder by reducing tantalum oxide with an alkaline earth metal such as magnesium, comprising the following steps:

[0010] (1) mixing tantalum oxide with an excess of an alkaline earth metal reducing agent and at least one alkali metal and / or alkaline earth metal halide in an amount of 10-200% by weight of the tantalum oxide, placing the mixture in a sealed reaction container, evacuating the air in the container, and placing the container in a heating furnace;

[0011] (2) raising the temperature of the heating furnace to 700-1000° C. and maintaining the temperature for, for example, 1-3 hours to allow the tantalum oxide to fully react with the reducing agent;

[0012] (3) After the insulation is completed, the temperature of the heating furnace is set at 600-750° C. (preferably 620-680° C., such as 640° C.), the heating furnace is evacuated, for example, to below 10 Pa, and the temperature is maintained under negative pressure (for example, for 1-10 hours);

[0013] (4) Then, an inert gas is filled into the reaction container to maintain a positive pressure in the reaction container, and then the reaction container is cooled to room temperature and passivated to obtain a mixture containing a halide and tantalum powder;

[0014] (5) separating tantalum powder from the obtained mixture, for example, by washing with water, washing with acid, filtering, or drying.

[0015] Wherein, in step (1), after the air is evacuated, the container is provided with a hydrogen-containing gas, for example, by introducing a hydrogen-containing gas, or by adding a liquid or solid (preferably solid) hydrogen-containing substance and allowing it to release hydrogen. Preferably, in the latter case, the hydrogen-containing substance is separated from other raw materials such as tantalum oxide powder, alkali metal and / or alkaline earth metal halide, which can be achieved, for example, by placing the hydrogen-containing substance (preferably hydrogen-containing tantalum powder) separately in a crucible.

[0016] Preferably, the hydrogen-containing substance is a substance that can release hydrogen at high temperature, such as tantalum powder adsorbing hydrogen (also called hydrogen-containing tantalum powder), hydrogen-containing niobium powder, hydrogen-containing titanium powder, and hydrogen-containing compounds.

[0017] The alkaline earth metal reducing agent described in step (1) is preferably magnesium, more preferably magnesium particles, more preferably 3N5 or above (purity above 99.95%) magnesium particles, and the higher the purity of the magnesium particles, the better. There is no restriction on the particle size of the magnesium particles. However, after a lot of research, the applicant found that magnesium particles with a particle size of 150-4000μm are more suitable for this technology, and the tantalum powder obtained by reduction has better pressure resistance. Magnesium particles in this particle size range are not only beneficial to the safety of the storage and transportation process of metallic magnesium, but also conducive to uniform mixing. If the magnesium particles are too fine, the activity is too strong and it is easy to spontaneously ignite; if the magnesium particles are too coarse, it is not conducive to uniform mixing and is not conducive to the optimization of tantalum powder performance. The amount of excess reducing agent added refers to the amount that exceeds the theoretical amount required to completely reduce tantalum oxide. Generally speaking, the theoretical amount required to completely reduce one kilogram of tantalum oxide is 0.273 kilograms. In the present invention, it is preferably 5-50% more than the theoretical amount, preferably 10-48%, more preferably 10-45%, and even more preferably 10-15%, 5-10%, or 15-20%.

[0018] In step (2), due to the heat of reduction, the tantalum powder inevitably undergoes a certain degree of sintering. The presence of hydrogen-containing gas in the container further enhances the sintering of the tantalum powder, thereby omitting a separate subsequent sintering step. Since the prior art often has a separate sintering step, the present invention undoubtedly simplifies the process. Moreover, the sintering and reduction under the conditions of the present invention are carried out simultaneously and cooperate with each other, making it easier to obtain tantalum powder with improved microstructure.

[0019] The added weight of the alkali metal and / or alkaline earth metal halide in step (1) is preferably 10-180% of the weight of tantalum oxide, preferably 25-120%, more preferably 70-120% or 100-180%, most preferably 15-80%, for example 25-80%. The alkali metal or alkaline earth halide is preferably analytically pure, preferably higher purity. The alkali metal or alkaline earth halide is preferably in particle form. There is no limitation on its particle size, but the applicant has found that particles of 70 μm-4000 μm are more suitable for this technology, and the tantalum powder obtained by reduction has better pressure resistance.

[0020] Preferably, the alkali metal or alkaline earth metal halide in step (1) is one or more of NaCl, KCl, KF, KI, and / or MgCl2. The alkali metal halide may be sodium chloride and / or potassium chloride. Preferably, it is a mixture of sodium chloride and potassium chloride, more preferably, the mass ratio of sodium chloride to potassium chloride in the mixture is 1:1-10, most preferably about 1:1.

[0021] Preferably, in step (1), one or more compounds containing B, P, and / or N elements may be added as additives to dope the tantalum powder. In terms of the amount of effective elements, the amount of B element added is preferably 1-100 ppm, more preferably 20-60 ppm; the amount of P element added is preferably 10-200 ppm, more preferably 30-90 ppm; the amount of N element added is preferably 300-2500 ppm, more preferably 500-1200 ppm. It should be understood that although compounds are added here, the effective elements are B, P, and / or N, so the amounts mentioned here are calculated based on the amounts of B, P, and / or N.

[0022] Preferably, in step (2), the heating furnace is heated to 750-1000° C. More preferably, the heating furnace is heated to 900-965° C.

[0023] Different from the inert atmosphere commonly used in the prior art, the hydrogen-containing gas used in step (1) is pure hydrogen or a mixture of hydrogen and an inert gas. The hydrogen can be gaseous hydrogen or hydrogen released by heating other liquid or solid hydrogen-containing substances. Importantly, the hydrogen-containing gas is used as the atmosphere in the present invention.

[0024] Although hydrogen is a common reducing agent, hydrogen cannot reduce tantalum oxide. In other words, hydrogen cannot act as a reducing agent in the present invention. However, the inventors unexpectedly discovered that since hydrogen strengthens the sintering that occurs during the reduction process, the process can be significantly simplified by omitting the sintering step. Moreover, the introduction of hydrogen-containing gas in an inert atmosphere can reduce the amount of alkaline earth metal added as a reducing agent and can also improve the overall electrical properties of the product.

[0025] Preferably, in step (1), a positive pressure is maintained in the reaction vessel. In the reaction vessel, the hydrogen partial pressure exceeds 0.050 KPa, preferably 0.1-200 KPa, more preferably 0.3-50 KPa, more preferably 10-20 KPa, more preferably 0.5-10 KPa or 10-15 KPa, more preferably 0.1-0.3 KPa. The inventors have found that too low a hydrogen partial pressure cannot fully promote the reduction effect, so from this perspective, the hydrogen partial pressure is preferably not too low; conversely, too high a hydrogen partial pressure will weaken the reduction effect, and from the perspective of ensuring the absolute safety of hydrogen use, it is preferred to avoid too high a hydrogen partial pressure.

[0026] Inert gas generally refers to rare gases, such as helium, neon, and argon. Although nitrogen is sometimes regarded as an inert gas due to its stable properties, in the art, due to the relatively high reduction temperature, nitrogen is very active at this high temperature, and it is generally considered not to be suitable for use as an inert protective gas. However, after extensive research, the inventors found that a small amount of nitrogen in the above-mentioned inert gas does not damage the inert protective atmosphere, and can also achieve nitrogen doping of tantalum powder. From the perspective of achieving a better nitrogen doping effect of tantalum powder, when a mixture of hydrogen-containing gas (such as pure hydrogen) and inert gas is used in step (1), it can preferably contain 0.5-10% nitrogen, based on the total amount of hydrogen-containing gas and inert gas.

[0027] In step (3), since the melting point of metallic magnesium is relatively high, it is difficult for magnesium vapor to diffuse to the outside of the reactor, but it condenses into a solid in the low temperature area of ​​the reactor, thereby achieving separation.

[0028] Preferably, in step (3), the temperature of the heating furnace is 600-750° C. More preferably, the heating furnace is heated to 620-680° C., for example, 640° C. Preferably, the heating furnace is evacuated to below 5 Pa, preferably below 0.5 Pa.

[0029] The hydrogen-containing gas in step (1) may be a mixture of hydrogen and an inert gas, and the inert gas in step (1) and step (4) may be the same or different. Preferably, in step (1) and / or (4), a positive pressure is maintained in the furnace. Preferably, in step (3), a positive pressure in the reactor is avoided, because a positive pressure is not conducive to the separation of excess alkaline earth metals such as magnesium.

[0030] Preferably, the method of the present invention further comprises heat treatment after step (5), such as high temperature and high vacuum heat treatment (or high temperature and high vacuum heat treatment after molten salt assisted sintering according to the invention of patent CN114210973B), oxygen reduction, acid washing, and then separating the tantalum powder by filtering and drying, so as to obtain tantalum powder suitable for making high-reliability tantalum capacitors. These treatments are all known processes in the prior art. In other words, these treatments can adopt any process known in the prior art. For example, the high-temperature and high-vacuum heat treatment and passivation here can adopt the methods provided by patents CN201110039272.9, CN201120077798.1, CN201120077680.9, CN201120077305.4, etc., the oxygen reduction can adopt the method provided by patent CN201420777210.7, and the pickling can adopt the methods provided by patents CN201210548101.3, CN201280077499.5, CN201210548008.2, etc.

[0031] As an alternative to doping N, P and / or B elements in step (1), the present invention may also include a separate step of doping these elements, for example, after step (5). Of course, raw materials containing these elements may also be used directly. These elements may also be added in the aforementioned high temperature and high vacuum heat treatment step. It is particularly preferred to add the P element. Adding the P element can increase the specific volume. As long as the total amount of P doping is controlled, the effect of increasing the specific volume is the same regardless of when it is added.

[0032] The tantalum powder of the above product is pressed into blocks, sintered, and energized under high voltage conditions. The electrical properties of the energizing blocks are tested, and it is found that the energizing blocks have good overall electrical properties. Therefore, the tantalum powder manufactured by the present invention is more suitable for making high-voltage and high-reliability tantalum capacitors.

[0033] Moreover, the process of the present invention is simple and easy to control. For example, in all steps of the present invention, microwaves are not used, and excessively high temperatures above 1000° C. are not used, and the proportion of alkaline earth metal used for reduction is lower. Therefore, the equipment used is also relatively simple, and the tantalum powder preparation process is safer.

[0034] Without being bound by general theories, combined with the theoretical analysis principle of powder liquid phase sintering, the inventor believes that the reason why the present invention achieves excellent results is as follows: in step (2), when hydrogen is present in the atmosphere, reduction is more likely to occur, and sintering is enhanced, making it easier to construct a spatial structure suitable for capacitors between tantalum powder particles, and the tantalum powder particles are uniform in size, smooth in particles, thick in sintering necks, and few in ultrafine particles. Thereafter, the obtained tantalum powder is subjected to high-temperature and high-vacuum heat treatment according to the prior art (or first subjected to molten salt assisted sintering and then high-temperature and high-vacuum heat treatment according to the invention of patent CN114210973B), deoxidation, and pickling treatment, and tantalum powder suitable for preparing high-voltage and high-reliability capacitors is obtained.

[0035] The “easier to construct a space structure suitable for capacitors” mentioned here means that after the obtained tantalum powder is pressed and sintered to make an anode block, there are no ultrafine pores in the obtained anode block. These ultrafine pores are not good for electrical properties, especially leakage current and ESR (equivalent series resistance).

[0036] The present invention also relates to tantalum powder prepared by the above method, an anode block made of the tantalum powder, and use of the tantalum powder and / or the anode block in making capacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The following drawings are provided for a better understanding of the present invention. These drawings are exemplary and are not intended to limit the scope of the present invention.

[0038] Figure 1 The scanning electron microscope picture of the tantalum powder obtained according to the present invention is given.

[0039] The accompanying figure illustrates that the obtained tantalum powder has a more uniform particle size, smooth particles, a thick sintering neck, and fewer ultrafine particles. DETAILED DESCRIPTION

[0040] In order to further illustrate the present invention, the preferred embodiments of the present invention are described below in conjunction with the examples, and it can be clearly seen that the objects, features and advantages of the present invention. However, these descriptions are only for further illustrating the features and advantages of the present invention, rather than for limiting the present invention. If the specific conditions are not specified in the examples, they are carried out under normal conditions. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0041] For the purpose of this specification, all numbers indicating the amount of ingredients, reaction conditions, etc. in the specification and claims should be understood as being modified by the term "about" in all cases, unless otherwise specified. Accordingly, the numerical parameters given in the following specification and the appended claims are approximate values, which may vary according to the desired properties that the present invention attempts to obtain, unless otherwise indicated. At least, and without intending to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should be interpreted at least in accordance with the number of reported significant figures and in accordance with conventional rounding techniques.

[0042] The analysis of impurity content in tantalum powder is carried out in accordance with the Chinese standard GB / T15076.1~15076.15, and the physical properties are carried out in accordance with the provisions of the industry standard YS / T573-2015. The test of electrical properties in tantalum powder is carried out in accordance with the provisions of the Chinese standard GB / T3137.

[0043] Example 1

[0044] Take 10.0kg of tantalum oxide, add 3.1kg of magnesium metal particles, and 3.0kg of potassium chloride (KCl), mix well and put into a reaction container, separate (i.e. extract) the air in the reaction container. Pass a mixture of hydrogen and argon into the reaction container, control the hydrogen partial pressure to 50KPa, keep the reaction container under positive pressure, put the reaction container into a heating furnace and heat it to 940℃, keep it warm for 2.0 hours, so that the tantalum oxide is fully reduced. Then, reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 3 hours, and stop evacuating. Then, pass argon into the reaction container and cool it down to room temperature, passivate it, take it out of the furnace after passivation, and the magnesium metal is stable without ignition and smoke when it is taken out of the furnace; then, wash, pickle, filter and dry the obtained mixture of halide and tantalum powder to separate the tantalum powder.

[0045] Then, the tantalum powder was doped with 50 ppm P and heated at 1450 °C and below 5.0 × 10 -3Pa, high temperature and high vacuum heat treatment is carried out for 1.0 hour, and then oxygen reduction and acid washing are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 1, and other conditions are in accordance with the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 250V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, after using 30% H2SO4 solution for testing, 10% H3PO4 solution is used for testing, and the measured results are listed in Table 1.

[0046] Example 2

[0047] Take 10.0kg of tantalum oxide, add 3.85kg of magnesium metal particles, and add 3.0kg of potassium chloride (KCl), mix well and put into a reaction container, and separate the air in the reaction container. Pass a mixed gas of hydrogen and argon into the reaction container, control the hydrogen partial pressure to 0.5KPa, and keep the reaction container under positive pressure. Put the reaction container into a heating furnace and heat it to 940℃, keep it warm for 2.0 hours, then reduce the temperature to 650℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 8 hours, and stop evacuating. Then, pass argon into the reaction container and cool it down to room temperature, and passivate it. After the passivation is completed, take it out of the furnace. When it is taken out of the furnace, the magnesium metal is stable and there is no ignition and smoke. The obtained halide and tantalum powder mixture is washed with water, acid-washed, filtered, and dried to separate the tantalum powder.

[0048] Then, the tantalum powder was doped with 50 ppm P and heated at 1450 °C and below 5.0 × 10 -3 Pa, high temperature and high vacuum heat treatment is carried out for 1.0 hour, and then oxygen reduction and acid washing are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 1, and other conditions are in accordance with the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 250V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, after using 30% H2SO4 solution for testing, 10% H3PO4 solution is used for testing, and the measured results are listed in Table 1.

[0049] Example 3

[0050] Take 10.0kg of tantalum oxide, add 3.50kg of magnesium metal particles, and at the same time add 3.0kg of potassium chloride (KCl), mix well and put into a reaction container, and separate the air in the reaction container. Pass a mixed gas of hydrogen and argon into the reaction container, control the hydrogen partial pressure to 100KPa, and keep the reaction container under positive pressure. Put the reaction container into a heating furnace and heat it to 940℃, keep it warm for 2.0 hours, then reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 5 hours, and stop evacuating. Then, pass argon into the reaction container and cool it down to room temperature, and passivate it. After the passivation is completed, take it out of the furnace. When it is taken out of the furnace, the magnesium metal is stable and there is no ignition or smoke. The obtained halide and tantalum powder mixture is washed with water, acid-washed, filtered, and dried to separate the tantalum powder.

[0051] Then, the tantalum powder was doped with 50 ppm P and heated at 1450 °C and below 5.0 × 10 -3 Pa, high temperature and high vacuum heat treatment is carried out for 1.0 hour, and then oxygen reduction and acid washing are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 1, and other conditions are in accordance with the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 250V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, after using 30% H2SO4 solution for testing, 10% H3PO4 solution is used for testing, and the measured results are listed in Table 1.

[0052] Example 4

[0053] Take 10.0kg of tantalum oxide, add 3.90kg of magnesium metal particles, and add 2.0kg of potassium chloride (KCl), mix well and put into a reaction container, and separate the air in the reaction container. Pass a mixed gas of hydrogen and argon into the reaction container, control the hydrogen partial pressure to 0.1KPa, and keep the reaction container under positive pressure. Put the reaction container into a heating furnace and heat it to 940℃, keep it warm for 2.0 hours, then reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 7 hours, and stop evacuating. Then, pass argon into the reaction container and cool it down to room temperature for passivation treatment. After passivation, take it out of the furnace. When it is taken out of the furnace, the magnesium metal is stable and there is no ignition and smoke. Wash the obtained halide and tantalum powder mixture with water, pickle, filter, and dry it to separate the tantalum powder.

[0054] Then, the tantalum powder was doped with 50 ppm P and heated at 1450 °C and below 5.0 × 10 -3Pa, high temperature and high vacuum heat treatment is carried out for 1.0 hour, and then oxygen reduction and acid washing are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 1, and other conditions are in accordance with the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 250V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, after using 30% H2SO4 solution for testing, 10% H3PO4 solution is used for testing, and the measured results are listed in Table 1.

[0055] Example 5

[0056] Take 10.0kg of tantalum oxide, add 3.1kg of metal magnesium particles, and at the same time add 3.0kg of potassium chloride (KCl), mix well and put into a reaction container, and separate the air in the reaction container. Pass a mixed gas of hydrogen and argon into the reaction container, control the hydrogen partial pressure to 0.3KPa, and keep the reaction container under positive pressure. Put the reaction container into a heating furnace and heat it to 940℃, keep it warm for 2.0 hours, then reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 3 hours, and stop evacuating. Then, pass argon into the reaction container and cool it down to room temperature for passivation treatment. After the passivation is completed, take it out of the furnace. When it is taken out of the furnace, the metal magnesium is stable and there is no ignition and smoke phenomenon; wash the obtained halide and tantalum powder mixture with water, pickle, filter, and dry it to separate the tantalum powder.

[0057] Then, the tantalum powder was doped with 50 ppm P and heated at 1450 °C and below 5.0 × 10 -3 Pa, high temperature and high vacuum heat treatment is carried out for 1.0 hour, and then oxygen reduction and acid washing are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 1, and other conditions are in accordance with the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 250V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, after using 30% H2SO4 solution for testing, 10% H3PO4 solution is used for testing, and the measured results are listed in Table 1.

[0058] Example 6

[0059] Take 10.0kg of tantalum oxide, add 3.1kg of metal magnesium particles, and add 1.5kg of potassium chloride (KCl) and 1.5kg of sodium chloride (NaCl), mix well and put into a reaction container, separate the air in the reaction container. Pass a mixed gas of hydrogen and argon into the reaction container, control the hydrogen partial pressure to 1.0KPa, keep the reaction container under positive pressure, put the reaction container into a heating furnace and heat it, raise the temperature to 940℃, keep it warm for 2.0 hours, then reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 3 hours, stop evacuating, then pass argon into the reaction container and cool it down to room temperature, passivate it, take it out of the furnace after passivation, and the metal magnesium is stable without ignition and smoke when it is taken out of the furnace; wash the obtained halide and tantalum powder mixture with water, pickle, filter, dry, and separate the tantalum powder.

[0060] Then, the tantalum powder was doped with 50 ppm P and heated at 1450 °C and below 5.0 × 10 -3 Pa, high temperature and high vacuum heat treatment is carried out for 1.0 hour, and then oxygen reduction and acid washing are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 1, and other conditions are in accordance with the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 250V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, after using 30% H2SO4 solution for testing, 10% H3PO4 solution is used for testing, and the measured results are listed in Table 1.

[0061] Example 7

[0062] Take 10.0kg of tantalum oxide, add 3.1kg of metal magnesium particles, and add 1.5kg of potassium chloride (KCl) and 1.5kg of sodium chloride (NaCl), mix well and put into a reaction container, put another crucible, put 1.5kg of tantalum powder containing 3500ppm of hydrogen in the crucible, and separate the air in the reaction container. Pass argon into the reaction container, keep the reaction container under positive pressure, put the reaction container into a heating furnace and heat it to 940℃, keep it warm for 2.0 hours, then reduce the temperature to 640℃ and evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 3 hours, stop evacuating, then pass argon into the reaction container and cool it down to room temperature, passivate it, take it out of the furnace after passivation, and the metal magnesium is stable without ignition and smoke when it is taken out of the furnace; wash the obtained halide and tantalum powder mixture with water, pickle, filter, dry, and separate the tantalum powder.

[0063] Then, the tantalum powder was doped with 50 ppm P and heated at 1450 °C and below 5.0 × 10 -3Pa, high temperature and high vacuum heat treatment is carried out for 1.0 hour, and then oxygen reduction and acid washing are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 1, and other conditions are in accordance with the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 250V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, after using 30% H2SO4 solution for testing, 10% H3PO4 solution is used for testing, and the measured results are listed in Table 1.

[0064] Comparative Example 1

[0065] Take 10.0kg of tantalum oxide, add 5.46kg of metal magnesium particles, and add 2.5kg of potassium chloride (KCl) and 2.5kg of sodium chloride (NaCl), mix well and put into a reaction container, and separate the air in the reaction container. Only argon gas is introduced into the reaction container, and the reaction container is placed in a heating furnace and heated under positive pressure conditions, and the temperature is raised to 940°C, and the temperature is kept for 1.0 hour, and then the temperature is reduced to 650°C for evacuation, and the pressure in the reaction container is reduced to 5.7Pa, and the temperature is kept for 8 hours, and the evacuation is stopped, and argon gas is introduced into the reaction container again to maintain the temperature under positive pressure and raise to 940°C, and the temperature is kept for 3 hours. After the insulation is completed, the temperature is lowered to room temperature and passivation treatment is carried out. After the passivation is completed, the metal magnesium is taken out of the furnace. When it is taken out of the furnace, the metal magnesium catches fire and smokes; the obtained halide and tantalum powder mixture is washed with water, acid-washed, filtered, and dried to separate the tantalum powder.

[0066] Then, the tantalum powder was doped with 50 ppm P and heated at 1450 °C and below 5.0 × 10 -3 Pa, high temperature and high vacuum heat treatment is carried out for 1.0 hour, and then oxygen reduction and acid washing are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 1, and other conditions are in accordance with the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 250V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, after using 30% H2SO4 solution for testing, 10% H3PO4 solution is used for testing, and the measured results are listed in Table 1.

[0067] Table 1 Electrical properties of finished tantalum powder

[0068]

[0069] From Table 1 we can see that:

[0070] After the present invention reduces the amount of magnesium metal used, the manufacturing of tantalum powder can be energized under a high voltage condition of 250V (the prior art generally uses a voltage below 200V), and the resulting energizing block has a high specific capacity, and in a specific capacitance test, the difference between the test results using a 30% H2SO4 solution and that using a 10% H3PO4 solution is relatively small, and a higher breakdown voltage is shown in a breakdown voltage test.

[0071] It can also be seen from Table 1 that the anode block made of the tantalum powder of the present invention has a smaller difference in specific capacitance after energization using different acid solutions. It is generally believed that phosphoric acid and sulfuric acid have different surface tensions and different abilities to penetrate into the ultrafine pores in the anode block. Therefore, the difference in specific capacitance reflects the presence of ultrafine pores in the anode block. Therefore, this proves that the use of the tantalum powder according to the present invention can obtain an anode block with fewer ultrafine pores and a better microstructure.

Claims

1. A method for preparing tantalum powder by reducing tantalum oxide with an alkaline earth metal such as magnesium (preferably magnesium particles), characterized in that The method comprises a reduction and heat preservation process in a hydrogen-containing atmosphere, preferably, the hydrogen-containing atmosphere is pure hydrogen or a mixture of hydrogen and an inert gas; and / or The hydrogen-containing gas is obtained by introducing a gaseous hydrogen-containing gas, or by adding a hydrogen-containing substance and allowing it to release hydrogen.

2. A method for preparing tantalum powder by reducing tantalum oxide with an alkaline earth metal such as magnesium (preferably magnesium particles), comprising the following steps: (1) Tantalum oxide is mixed with an excess of an alkaline earth metal reducing agent, and at the same time, 10-200% by weight of at least one alkali metal and / or alkaline earth metal halide is mixed into the mixture, and the mixture is placed in a sealed reaction container, the air in the container is evacuated, and the container is placed in a heating furnace. (2) raising the temperature of the heating furnace to 700-1000° C. (more preferably, raising the temperature to 750-970° C., and more preferably, raising the temperature of the heating furnace to 900-950° C.), and then maintaining the temperature for, for example, 1 h to 3 h, so that the tantalum oxide and the reducing agent undergo a full reduction reaction; (3) After the insulation is completed, the temperature is lowered to 600-750° C. (preferably, the heating furnace is cooled to 640-680° C.), and the heating furnace is evacuated, for example, to below 10 Pa, for example, 5 Pa, preferably to below 0.5 Pa, and the temperature is maintained under negative pressure to separate the excess metal magnesium from the tantalum powder mixture; (4) Then, an inert gas is filled into the reaction container to maintain a positive pressure in the reaction container, and then the reaction container is cooled to room temperature and passivated to obtain a mixture containing a halide and tantalum powder; (5) separating tantalum powder from the obtained mixture, for example, by washing with water, washing with acid, filtering, or drying. Wherein in step (1), after the air is evacuated, the container is filled with a hydrogen-containing gas, for example, by introducing a hydrogen-containing gas (for example, pure hydrogen, or a mixture of hydrogen and an inert gas), or by adding a hydrogen-containing substance (for example, metallic tantalum adsorbed with hydrogen) and causing it to release hydrogen. Preferably, the hydrogen-containing gas contains 0.5-10% nitrogen.

3. The manufacturing method according to claim 2, characterized in that: The amount of reducing agent added in step (1) is 5-50% of the theoretical amount for complete reduction of tantalum oxide, preferably 10-48%, more preferably 10-45%, even more preferably 10-15%, 5-10%, or 15-20%.

4. The manufacturing method according to claim 2 or 3, characterized in that: The weight of the alkali metal chloride added in step (1) is 10-180% of the weight of tantalum oxide, preferably 25-120%, more preferably 70-120% or 100-180%, most preferably 15-80%, for example 25-80%.

5. The manufacturing method according to any one of claims 2 to 4, characterized in that: The alkali metal or alkaline earth metal halide in step (1) is a mixture of one or more of NaCl, KCl, KF, KI, MgCl2, preferably a mixture of NaCl and KCl, more preferably a mass ratio of sodium chloride to potassium chloride in the mixture is 1:1-10, most preferably about 1:

1.

6. The manufacturing method according to any one of claims 2 to 5, characterized in that: In step (1), one or more compounds containing B, P, and / or N elements are added as additives to dope the tantalum powder. Preferably, the amount of B element added is 1-100 ppm, more preferably 20-60 ppm, based on the amount of effective elements. and / or the added P element is 10-200ppm, more preferably 30-90ppm; And / or the added N element is 300-2500ppm, more preferably 500-1200ppm.

7. The manufacturing method according to claim 2, characterized in that: The hydrogen partial pressure of the hydrogen-containing gas in step (1) exceeds 0.050 KPa, preferably 0.1-200 KPa, more preferably 0.3-50 KPa, more preferably 0.3-20 KPa, even more preferably 0.5-2 KPa or 2-8 KPa, even more preferably 0.1-0.3 KPa.

8. The manufacturing method according to any one of claims 1 to 7, further comprising after step 5): High temperature and high vacuum heat treatment; Reduce oxygen, for example by adding a small amount of magnesium particles; and The separation is carried out, for example, by acid washing, filtering, and drying.

9. Tantalum powder produced by the production method according to any one of claims 1 to 8, and an anode block made of the tantalum powder.

10. Use of the tantalum powder according to claim 9 in the manufacture of capacitors.

Citation Information

Patent Citations

  • Thermal treatment method of tantalum powder

    CN102120258A

  • Stirring water-washing method and device for producing tantalum powder by reducing potassium fluotantalate via metallic sodium

    CN102990076B

  • Method for purifying tantalum powder

    CN102994780B

  • Niobium or tantalum based powder produced by the reduction of the oxides with a gaseous metal

    CN105033283A

  • Method and apparatus for purifying target powder

    CN105051223B